Pilot feasibility randomized clinical trial of negative-pressure wound therapy versus usual care in patients with surgical wounds healing by secondary intention. Issue 3 (23rd April 2018) - Arundel, C.; Fairhurst, C.; Corbacho-Martin, B.; Buckley, H.; Clarke, E.; Cullum, N.; Dixon, S.; Dumville, J.; Firth, A.; Henderson, E.; Lamb, K.; McGinnis, E.; et al.
Graphical Abstract: Abstract: Background: Surgical wounds healing by secondary intention (SWHSI) are increasingly being treated with negative-pressure wound therapy (NPWT) despite a lack of high-quality research evidence regarding its clinical and cost-effectiveness. This pilot feasibility RCT aimed to assess the methods for and feasibility of conducting a future definitive RCT of NPWT for the treatment of SWHSI. Methods: Eligible consenting adult patients receiving care at the study sites (2 acute and 1 community) and with a SWHSI appropriate for NPWT or wound dressing treatment were randomized 1 : 1 centrally to receive NPWT or usual care (no NPWT). Participants were followed up every 1–2 weeks for 3 months. Feasibility (recruitment rate, time to intervention delivery) and clinical (time to wound healing) outcomes were assessed. Results: A total of 248 participants were screened for eligibility; 40 (16·1 per cent) were randomized, 19 to NPWT and 21 to usual care. Twenty-four of the 40 wounds were located on the foot. Participants received NPWT for a median of 18 (range 0–72) days. Two participants in the NPWT group never received the intervention and 14 received NPWT within 48 h of randomization. Five participants in the usual care group received NPWT during the study. Ten of the 40 wounds were deemed to have healed during the study. Conclusion: A full-scale RCT to investigate the clinical and cost-effectiveness of NPWT for SWHSI is feasible. This study identified crucial information on recruitment rates and data collection methods to consider during the design of a definitive RCT. Registration number: ISRCTN12761776 (http://www.iscrtn.com )